Photovoltaic and electrophysical properties of plasmon-enhanced organic solar cells - A.K. Zeinidenov; N.Kh. Ibrayev (Қарағанды университетінің хабаршысы. Физика сериясы)
A technique for depositing plasmon silver nanoparticles into various functional layers of an organic solar cell has been developed. Analysis of the structure of nanoparticles was carried out according to electron microscopic images on an electron microscope MIRA 3 LMU, Tescan. Electron microscopic analysis showed the presence of spherical silver nanoparticles. The size of silver nanoparticles was ~ 100–200 nm. The frequency of plasmon resonance lies in the region of 451-457 nm. The microstructural and optical properties of nanocomposite materials obtained are studied. The film thickness of the deposited photoactive layer P3HT: PCBM is 229 nm, the thickness of the deposited silver film is 87 nm, respectively. It is shown that the absorption band of silver nanoparticles on the ITO surface has a maximum at the wavelength of 457 nm. For silver nanoparticles on the P3HT / PCBM surface, the maximum wavelength is shifted to the shortwave region at 451 nm. The photovoltaic and electrotransport properties of film polymer compositions based on P3NT: RSVM and silver nanoparticles are studied. Measurement of the volt-ampere characteristic of the cells was carried out by illuminating the cell from the side of the conducting layer of the ITO. It is shown that the deposition of silver nanoparticles on the ITO surface increases the PSC efficiency by 1.7 times. When the film of silver nanoparticles is positioned between PEDOT / PSS and the photoactive layer of P3HT / PCBM, the efficiency is reduced by approximately 1.8 times. In the presence of silver nanoparticles, a further reduction in the cell efficiency is observed on the surface of the P3HT / PCBM photoactive layer. Doping of silver nanoparticles into the photoactive layer of P3HT / PCBM also leads to a decrease in the cell efficiency. The electron transport properties of a solar cell with a bulk heterojunction were studied using the method of electrochemical impedance spectroscopy (EIS). It is shown that a significant increase in the cell efficiency is observed when silver nanoparticles are deposited on the ITO surface. Precipitation of silver nanoparticles on the surface of the PEDOT:PSS layer and doping them into the P3HT: PCBM volume reduces the conversion of solar energy into electrical energy.